0381 Actigraphy Measures of Maternal Sleep Disruption are Associated with the Inability to Sustain Sensitive Caregiving in the Postpartum Period. (12th April 2019) - Rangel, Elizabeth; King, Lucy; Simpson, Norah; Manber, Rachel
Abstract: Introduction: During postpartum, mothers experience disruptions in their sleep related to their infant. Maternal sensitivity, or the mother's ability to accurately perceive and interpret her infant's cues and respond to them, is central for the development of a healthy parent-child relationship in infancy. Using data collected in a RCT of CBT for insomnia for pregnant women, we examined the possibility that poor maternal sleep, measured via Actigraphy, will be associated with reduced maternal sensitivity during the postpartum period. Methods: At 18 weeks postpartum, mothers completed the Insomnia Severity Index (ISI), one week of the Actiwatch™, and concurrent Consensus Sleep Diaries. Mothers were recorded during a ten-minute "free play" with their infants. The recordings were coded using the infant adaptation of the Parent-Child Interaction Rating Scale across 5 two minute intervals. Results: Mixed effects modeling revealed that maternal wake time after sleep onset (WASO) was not associated with mean maternal sensitivity, but it was related to the change in maternal sensitivity across the five intervals (p=.018). Post-hoc simple slopes analyses revealed that sensitivity of mothers with high WASO (≥90 min) demonstrated greater decrease across the free play intervals than mothers with low WASO (≤30 min) (B=-0.01, SE=0.04, t(217.10)=-3.58, p=<.001). The effect of the number of wake bouts mirrored the effect of WASO. Maternal sensitivity across the free play decreased more among mothers with a greater number of wake bouts (B =-0.16, SE=0.05, t(217.15)=-3.27, p=.001, 95% CI[-0.25, -0.06]). Neither ISI nor sleep duration were associated with overall levels or with the trajectory of maternal sensitivity across the free play intervals (p-values ≥.18). Conclusion: The results indicate that although mothers with poorer sleep continuity did not demonstrate lower levels of sensitivity overall, they struggled to sustain sensitivity across the interaction. Since both infant care and time to return to sleep contribute to maternal time awake after sleep onset, future research will need to examine the relative contribution of each in order to design interventions to improve maternal sensitivity. Support (If Any): NR013662